The relationship between students' absorptive capacity and motivation, and knowledge transfer effectiveness in Malaysian community colleges / Mohammad Nazri Mohd Nor - Mohd Nor, Mohammad Nazri (2012)
Apart from public and private universities, community colleges serve as alternative paths for SPM school leavers to further their education. However, low community colleges students' previous academic achievement and the fact that the students formed the highest rate of graduate unemployment among other higher learning institutions have raised questions on the effectiveness of knowledge transfer in Malaysian community colleges. Thus, the main objective of this study is to determine the relationship between students' absorptive capacity and motivation, and knowledge transfer effectiveness in Malaysian community colleges. A total of 387 selfadministered questionnaires were sent in August 2010 to respondents in 18 colleges by using cluster random sampling technique. With a valid response of 87 per cent (338 respondents), descriptive, multiple and hierarchical regression analyses were conducted using the Statistical Package of Social Science (SPSS) version 17.0. With regard to its main objective, empirical evidence indicated that hypotheses in relation to both students' absorptive capacity and motivation effect on knowledge transfer effectiveness were statistically significant. For subsequent objectives, parental involvement was found to have a statistically significant positive moderating impact on the relationship between students' absorptive capacity and knowledge transfer effectiveness except for students' motivation. However, lecturer support showed no statistically significant moderating impact on both of the relationships. The results suggest that students' absorptive capacity and students' motivation need to be improved to increase the effectiveness of knowledge transfer, such as by providing more encouragement, awareness and effective intervention programmes. In addition to that, though there was only one situation where moderating impact of parental involvement was significant, in reality the impact of lecturer support and parental involvement in increasing knowledge transfer effectiveness may have a different bearing. Hence, this needs to be investigated further in future research. In a nutshell, this study could provide insights and understanding towards improving knowledge transfer effectiveness in Malaysian community colleges which is important for enhancing students' academic performance and their future job prospects. At the same time, the perceived academically underprepared students will not be left out in the quest for better knowledge that would enhance economic development of the nation. Producing better quality students would help improve the Malaysian community colleges' image and increase the employment prospects among its graduates. Indeed, this would help to produce credible higher learning institutions and indirectly help Malaysia to leap forward towards becoming a developed nation.